Consideraciones de diseño para subsistemas de estaciones base en entornos GSM para la CNT EP Los Ríos. Año 2015. - Solorzano Moreno, Cristhian Augusto (2015)
This work is oriented to the analysis necessary to optimize design for base station subsystems in GSM systems for CNT EP Los Ríos considerations, the high cost of these technologies is necessary to develop methods or means of appropriate design that ensure optimal performance of these networks to provide fault them when they are at full capacity. The problems and the current situation of designs base station subsystem described, objectives, assumptions, rationale and expected changes to make this project are described. Within the framework reference to the base station subsystem is the study of reliable tools for the analysis of the spread, the network dimensioning and proposes steps to improve the design of the base station subsystem. Then the respective legal basis, it is considered that the organic law on telecommunications in force will be described. The methodology of the research method used in this project, the dependent and independent variables of the current problems is analyzed is determined. Analysis of propagation models will be made, which will help us with their advantages and disadvantages which one is more suitable for the preparation of the proposed design Finally the proposed alternative project in which design considerations for a base station subsystem for GSM environments CNT EP Los Ríos will be made is presented.